The Effect of Applying Jigsaw Technique on Students’ Achievement in Reading Comprehension of Narrative Tex - Julita Sembiring (The Explora, 2021)
Reading is one of the important skills in learning English. Reading can be as a language tool for communication and give information. In reading, students do not only read a text but also have to be able to comprehend the text and to know main idea of the text. In reality, many students have weakness in reading comprehension, so the writer will conduct the Jigsaw Technique in teaching reading. In this thesis the writer report on the effect of Jigsaw Technique on reading comprehension. The purpose of this study is to find out whether Jigsaw Technique affect students on reading comprehension significantly. The Technique that used in the research is quantitative by doing experimental design. The result shows that the scores of t-test (3.90) > t-table (1,67), it means that Jigsaw Technique can improve students’ achievement in reading comprehension. So, the writer concluded that there was significant effect of Jigsaw Technique on students’ Reading comprehension. And the last the writer gives suggestion that teachers should apply strategy especially Jigsaw Technique with affects the ability of students in reading comprehension.